PENYULUHAN HAK KESEJAHTERAAN ANAK BAGI ANAK YATIM PIATU SEBAGAI BAGIAN DARI SISTEM EKONOMI ISLAM DI DESA CIBATOK II, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Tri Aditya Putra; Tubagus Rifqy Thantawi; Bayu Purnama Putra (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract Partners in this Community Service activity are santri at the Al Hidayah Islamic Boarding School, whose address is Jl. Kp. Cibinong No.12, Kec. Ciomas, Bogor, West Java. This community service activity starts from June 2021 to July 2021 which begins with an audience, a meeting to discuss themes, signing of collaboration and implementing education / counseling. Pesantren as the oldest education in Indonesia is growing rapidly and is big. Its development is not only textual, but also more up-to-date with the times, with the aim of preparing more advanced students or santri, not only experts in the field of religion, but also on governance, which is also encouraged by holding education in Islamic boarding schools. Protection of children has been regulated in law, namely Law No.23 of 2002 concerning Child Protection (PA). The Law has regulated the rights of children, the implementation of the obligations and responsibilities of parents, family, society, government and the state to provide protection for children. The protection referred to, as stated in article 1 paragraph 2 of the CL Law,